(untitled) (Journal of the Bangladesh Agricultural University, 2020)
Health related quality of life (HRQOL) is an individual’s or a group’s perceived physical and mental health over time. This study has carried out to find out the food insecurity, nutritional status and health related quality of life (HRQOL) of female garment factory workers and also the relationship of health related quality of life with food insecurity and nutritional status of female garment factory workers. This study has found that 71.9 percent female garment factory workers are food insecure and the percentage of being food secure is 28.1 percent. According to the Body Mass Index (BMI) classification for Asian people, 60.6 percent workers are in the normal range (17.5-22.9kg/m2), while 27.2 percent are in the overweight (23-27.9kg/m2) and 4.1 percent are in obese category (≥28 kg/m2), and 8.1 percent are underweight (<17.5 kg/m2) and with the waist circumference (WC) classification, 24.2 percent of them are in the normal range (WC<80 cm.) and 75.8 percent (WC≥80 cm.) are at risk of obesity category. Measuring the HRQOL of female garment factory workers, it has found that 84.6 percent respondents have restricted their daily activities for physical problems, 82.9 percent female workers have faced difficulties in running social activities and 86.6 percent contributors have not worked properly due to emotional problems. There are statistically significant differences between food secure and insecure respondents in physical function, general health, vitality and mental health domains (P<0.05). Association of health related quality of life (HRQOL) within the Asian classified BMI categories, normal weight (17.5-22.9 kg/m2) female garment factory workers show better health situation compared with obese group (≥28 kg/m2). Statistically significant differences have found in physical activities and role physical (P<0.05). Normal waist circumference participants have higher scores on physical function, role physical and bodily pain scales (P<0.05). J Bangladesh Agril Univ 18(2): 492–501, 2020 https://doi.org/10.5455/JBAU.82000